Tah?lîl al-Khat?â’ fî al-‘Arabiyyah al-Mant?ûqat ‘inda T?alabat al-Indunisiyyîn - Adrianadi Adrianadi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
Means of communication between people is the language, and every language in the world has a different aspect, it depends on the characteristics of the language and the language system, both in terms of sound and grammar and the structure and semantics. Many students of Indonesia, impressed "difficult" when learning Arabic. This may be due to differences in language systems between Arabic and Indonesian. This article will analyze faults Indonesian students when using the Arabic language as a means of communication, in the hope that students can find out the cause as well as the types of errors in the language. So for the future can avoid those mistakes.